Characterization of common Nigerian cowpea (Vigna unguiculata L. Walp) varieties (2002)
Eight cowpea (Vigna unguiculata L. Walp) varieties namely Olo-1, Olo-2, Baujara, Karadua, Manyan Fari, Kananado Yar and Akidi were characterized based on their physical and functional properties. Physical properties investigated include seed-weight, length to diameter ratio, specific gravity, bulk density, angle of repose and percentage of seed coat. The functional properties examined were water absorption capacity, swelling capacity, cooking time and moisture content. The result of both physical and functional properties showed significant differences (P = 0.05) among the cowpea varieties. The specific .gravity ranged from 1.05 to 1.19 with Kananado Yar, Kananado Fari and Banjara having higher values than others, while water absorption capacity ranged from 1.14 to 1.60 g H2O/g sample for Kananado Fari and Banjara varieties respectively. Apparently, the outcome of this work would provide a basis for upgrading local techniques of cowpea processing in Nigeria